Co-fermentation of xylose and glucose from ionic liquid pretreated sugar cane bagasse for bioethanol production using engineered xylose assimilating yeast. (September 2019) - Amoah, Jerome; Ogura, Kazuma; Schmetz, Quentin; Kondo, Akihiko; Ogino, Chiaki
Abstract: An efficient method to co-ferment xylose and glucose in ionic liquid was developed via effective simultaneous saccharification and fermentation of sugar cane bagasse. Fermentation of pure xylose to ethanol in ionic liquids by two engineered xylose-assimilating Saccharomyces cerevisiae yeast strains, XR-XDH (Xylose Reductase-Xylitol Dehydrogenase pathway strain) and XI (Xylose isomerase pathway strain) resulted in lower conversion compared to ionic liquid-free medium. The ionic liquids however contributed to a higher saccharification efficiency of sugar cane bagasse. Among the five ionic liquids tested, 1-butyl-3-methylpyridinium chloride ([Bmpy][Cl]) yielded the highest saccharification efficiency resulting in 0.7 g/L xylose and 2.3 g/L glucose which are 5 and 2-folds, respectively, higher than the absence of ionic liquid. The high saccharification efficiency in [Bmpy][Cl] resulted in a more efficient assimilation of xylose from sugar cane bagasse in a simultaneous saccharification and fermentation process leading to 84.0% ethanol yield compared to 26.7% produced by the reference strain in the absence of ionic liquid. This efficient method for co-fermentation of xylose and glucose to ethanol will further enhance the effective utilization of biomass as a resource for bioethanol production. Graphical abstract: A xylose-assimilating yeast capable of co-fermenting xylose and glucose in ionic liquid was developed to maximise bioethanol production from lignocellulosic biomass. Image 1 Highlights: Construction of 2 xylose assimilating yeast strains, XI and XR-XDH. [Bmpy][Cl] resulted in the highest glucose and xylose yield from sugarcane bagasse. Simultaneous saccharification and fermentation was carried out in ionic liquids. 69.9% of xylose produced from sugarcane bagasse was assimilated by XI strain. Conversion was improved by more than 3-folds to achieve 84% ethanol yield.